1987
DOI: 10.1073/pnas.84.23.8296
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of rat cardiac beta-adrenergic and muscarinic cholinergic receptors obtained by automated DNA sequence analysis: further evidence for a multigene family.

Abstract: Two cDNA clones, X RHM-MF and X RHB-DAR, encoding the muscarinic cholinergic receptor and the 13-adrenergic receptor, respectively, have been isolated from a rat heart cDNA library. The cDNA clones were characterized by restriction mapping and automated DNA sequence analysis utilizing fluorescent dye primers. The rat heart muscarinic receptor consists of 466 amino acids and has a calculated molecular weight of 51,543. The rat heart P-adrenergic receptor consists of 418 amino acids and has a calculated molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(54 citation statements)
references
References 20 publications
1
53
0
Order By: Relevance
“…In contrast, the exchange of this region between mAChR I and mAChR II does not significantly;affect the antagonist binding proper-ties of the two mAChR subtypes. The amino acid sequence of the putative cytoplasmic portion between the proposed transmembrane segments V and VI is divergent among the mAChR subtypes [2,12,[16][17][18]30,31].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the exchange of this region between mAChR I and mAChR II does not significantly;affect the antagonist binding proper-ties of the two mAChR subtypes. The amino acid sequence of the putative cytoplasmic portion between the proposed transmembrane segments V and VI is divergent among the mAChR subtypes [2,12,[16][17][18]30,31].…”
Section: Resultsmentioning
confidence: 99%
“…In 1986, Hood and co-workers (5) described an improvement in the Sanger sequencing method that included attaching fluorescent dyes to the nucleotides, which permitted them to be sequentially read by a computer. The first automated DNA sequencer, developed by Applied Biosystems in California in 1987, was shown to be successful when the sequences of two genes were obtained with this new technology (6). From early sequencing of human genomic regions (7), it became clear that cDNA sequences (which are reverse-transcribed from RNA) would be essential to annotate and validate gene predictions in the human genome.…”
mentioning
confidence: 99%
“…Mutants constructed with deletions of amino acids 179-187 in the second extracellular loop bound agonist and antagonist with reduced affinity, perhaps implying a role of this region either in the direct binding of the ligand or in the proper folding and transmembrane assembly of the receptor (4,25). Later studies demonstrated that four cysteine residues (Cys 1 06, Cys 1 84, Cys190, and Cys191) located in the extracellular domains of the f3zAR are involved in disulfide-bridging, important for agonist and antagonist interactions with the receptor (25)(26)(27).…”
Section: Hydrophilic Extracellular Domains-regions Involved In Propermentioning
confidence: 99%
“…The cloning of .B2AR cDNA from hamster (2), human (3), rat (4,5), and mouse (6), as well as the gene from human genomic DNA (7,8), has allowed deduction of the amino acid sequence and analysis of the primary structure of these proteins. The amino acid sequence and proposed membrane topography for the human f32AR is presented in Figure 1.…”
Section: Introductionmentioning
confidence: 99%